Globalización y desafíos para la pequeña agricultura en Costa Rica experiencias de organización y generación de servicios para el acceso a mercados - Francois Le Coq, Jean (Editorial Universidad Nacional (EUNA), 2014)
This work presents a proposal for a new research agenda for the rural areas of Costa Rica, based on new contexts, challenges and concepts, and with a series of public policy recommendations for the Costa Rican rural world.